El régimen legal de las tasas de interés en la legislación peruana - Castellares Aguilar, Rolando (Pontificia Universidad Católica del Perú, 2024)
Law No. 31143 has increased the Maximum Interest Rates to usury levels, especially for the sector outside the financial system; while operations within the financial system will no longer have interest rates freely determined by the parties, but rather some banking operations will be subject to Maximum Rates; while the other operations will have interest rates according to free supply and demand, thus generating a double regime for the operations of the financial system.On the other hand, the Maximum Interest Rates applicable to operations outside the financial system, such as the operations of the financial system subject to control, will have the same Maximum Rates, they will be determined semiannually; Therefore, these Maximum Rates will vary each semester, applying to the transactions agreed upon during that semester; all of which will generate complexity and conflicts between the parties.

La Ley No. 31143 ha incrementado las Tasas Máximas de Interés a niveles de usura, en especial para el sector ajeno al sistema financiero; mientras que las operaciones dentro del sistema financiero ya no tendrán tasas de interés de libre determinación por las partes, sino algunas operaciones bancarias estarán sujetas a Tasas Máximas; mientras que las demás operaciones tendrán tasas de interés según la libre oferta y demanda, generándose así un doble régimen para las operaciones dentro del sistema financiero.Por otro lado, las Tasas Máximas de Interés aplicables a las operaciones ajena al sistema financiero, como las operaciones propias del sistema financiero sujetas a control, tendrán las mismas Tasas Máximas, se determinarán semestralmente; por lo que cada semestre variarán estas Tasas Máximas, aplicándose a las transacciones que se acuerden en el curso de ese semestre; todo lo cual generará complejidad y conflictos entre las partes.
The Legal Regime of Interest Rates in Peruvian Legislation
Keywords: Maximum Compensatory and Moratorium Interest Rates; Tasas Máximas de Interés Compensatorio y Moratorio; https://purl.org/pe-repo/ocde/ford#5.05.00